Respostas

2013-06-06T12:16:08-03:00

sen ( A - B ) = sen (A) x cos (B) - sen (B) x cos (A)

e

cos ( A - B ) = cos (A) x cos (B) + sen (A) x sen (B)

A partir dai você consegue calcular, pois

sen( 15 ) = sen ( 45 - 30 ) = 
= sen (45) x cos (30) - sen (30) x cos (45) =
= [ 1 / raiz(2) ] x [ raiz(3) / 2 ] - [ 1 / 2 ] x [ 1 / raiz(2) ] =
= [ raiz(3) - 1 ] / [ 2 x raiz(2) ]

e

cos( 15 ) = cos ( 45 - 30 ) =
= cos (45) x cos (30) + sen (30) x sen (45) =
= [ 1 / raiz(2) ] x [ raiz(3) / 2 ] + [ 1 / 2 ] x [ 1 / raiz(2) ] =
= [ raiz(3) + 1 ] / [ 2 x raiz(2) ]

4 4 4